Life Cycle Management - Sonnemann, Guido; Margni, Manuele; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2015)
This book provides insight into the Life Cycle Management (LCM) concept and the progress in its implementation. LCM is a management concept applied in industrial and service sectors to improve products and services, while enhancing the overall sustainability performance of business and its value chains. In this regard, LCM is an opportunity to differentiate through sustainability performance on the market place, working with all departments of a company such as research and development, procurement and marketing, and to enhance the collaboration with stakeholders along a company’s value chain. LCM is used beyond short-term business success and aims at long-term achievements by minimizing environmental and socio-economic burden, while maximizing economic and social value.
Part I: Introducing Life Cycle Management -- Introduction: Life Cycle Management -- Life Cycle Management: Implementing Sustainability in Business Practice -- Life Cycle Management as a Way to Operationalize Sustainability Within Organizations -- How to Implement Life Cycle Management in Business? -- Life Cycle Sustainability Assessment: A Tool for Exercising due Diligence in Life Cycle Management -- Life Cycle Management: Labeling, Declarations and Certifications at the Product Level —Different Approaches -- Mainstreaming the Use of Life Cycle Management in Small and Medium Sized Enterprises Using a Sector Based and Regional Approach -- Part II: Advancing the Implementation of Life Cycle Management in Business Practice -- From Projects to Processes to Implement Life Cycle Management in Business -- How to Make the LCA Team a Business Partner -- Sustainability Improvements and Life Cycle Approaches in Industry Partnerships -- Sustainable Value Creation with Life Cycle Management -- Part III: Life Cycle Management as Part of Sustainable Consumption and Production Strategies and Policies -- Hotspots Analysis: Providing the Focus for Action -- From Sustainable Production to Sustainable Consumption.-Life Cycle Management Responsibilities and Procedures in the Value Chain -- Policy Options for Life Cycle Assessment Deployment in Legislation -- Part IV: Mainstreaming and Capacity Building on Life Cycle Management -- Taking Life Cycle Management Mainstream: Integration in Corporate Finance and Accounting -- Building Organizational Capability for Life Cycle Management -- Promoting Life Cycle Thinking, Life Cycle Assessment and Life Cycle Management Within Business in Brazil -- Mainstreaming Life Cycle Sustainability Management in Rapidly Growing and Emerging Economies Through Capacity-building.-Communication and Collaboration as Essential Elements for Mainstreaming Life Cycle Management.-Part V: Implementation and Case Studies of Life Cycle Management in Different Business and Industry Sector -- Exploring Challenges and Opportunities of Life Cycle Management in the Electricity Sector -- Life Cycle Management Applied to Urban Fabric Planning -- Implementing Life Cycle Engineering in Automotive Development as a Helpful Management Tool to Support Design for Environment -- Managing Life cycle Sustainability Aspects in the Automotive Industry -- Life Cycle Management as a Way to Operationalize the Creating Shared Value Concept in the Food and Beverage Industry: A Case Study.
Keywords: Sustainable development; Environmental management; Renewable energy resources; Environmental sciences; Sustainable Development; Environmental Management; Renewable and Green Energy; Environmental Science and Engineering